The impact of cognitive intelligence on implementing organizational strategy - علاء فرحان طالب; عواد كاظم شعلان; جنان مهدي الدهان (Iraqi Journal for Administrative Sciences, 2024)
Intelligence cognitive big impact when activity needs high levels of personal commitment, and self-confidence, and trust between individuals, freedom of communication, and proactive behavior. Or It's , countless types of emotions and behaviors, such as personal, anger, anxiety, fear, conflict of values, competition, etc., and often arise in a group project. Since it depends on the effectiveness of the performance of these organizations, particularly service organizations, to a large extent on the emotional and cognitive ability of the persons concerned performance. It facilitates the quality of work of persons and motives of intelligent group. So this study trying to theoretical and practical intellectual applied to study the possibility of using cognitive intelligence in the implementation of organizational strategy in order to detect the psychological and social foundations in the implementation of organizational strategy.